Highly Efficient Genome Editing of Murine and Human Hematopoietic Progenitor Cells by CRISPR/Cas9 - Michael C. Gundry; Lorenzo Brunetti; Angelique Lin; Allison E. Mayle; Ayumi Kitano; Dimitrios Wagner; Joanne I. Hsu; Kevin A. Hoegenauer; Cliona M. Rooney; Margaret A. Goodell; Daisuke Nakada (Cell Reports, 2016)
Summary: Our understanding of the mechanisms that regulate hematopoietic stem/progenitor cells (HSPCs) has been advanced by the ability to genetically manipulate mice; however, germline modification is time consuming and expensive. Here, we describe fast, efficient, and cost-effective methods to directly modify the genomes of mouse and human HSPCs using the CRISPR/Cas9 system. Using plasmid and virus-free delivery of guide RNAs alone into Cas9-expressing HSPCs or Cas9-guide RNA ribonucleoprotein (RNP) complexes into wild-type cells, we have achieved extremely efficient gene disruption in primary HSPCs from mouse (>60%) and human (∼75%). These techniques enabled rapid evaluation of the functional effects of gene loss of Eed, Suz12, and DNMT3A. We also achieved homology-directed repair in primary human HSPCs (>20%). These methods will significantly expand applications for CRISPR/Cas9 technologies for studying normal and malignant hematopoiesis. : Gundry et al. develop an efficient and simple method implementing CRISPR/Cas9-mediated gene disruption and HDR in murine and human HSPCs. This method enables quick evaluation of the function of genes by performing in vitro or transplantation assays using the modified HSPCs. Keywords: HSC, hematopoietic stem cells, progenitor, human CD34, genome editing, CRISPR/Cas9, sgRNA, homology-directed repair, gene therapy, transplantation